Dose-effect relationship of perindopril 10, 14 and 20mg assessed by urine and plasma AcSDKP levels in mildly sodium-depleted healthy volunteers - Monge, Matthieu; Paquet, Valérie; Bergerot, Damien; Zhygalina, Valentina; Blanchard, Anne (International journal of cardiology, 2016)
We describe a pharmacodynamic study of the dose-effect relationship of perindopril arginine at 10, 14, and 20mg with in vivo angiotensin-converting enzyme (ACE) activity, assessed by urine and plasma AcSDKP levels, as well as the effect on plasma active renin concentrations and blood pressure. This randomized, double-blind, four-period, crossover study involved single-dose administration of perindopril arginine (10, 14, and 20mg or placebo) to 32 healthy male normotensive mildly sodium-depleted volunteers. Blood and urine were collected over 48h for AcSDKP, ACE activity, and plasma active renin measurements. There were dose-related increases in urinary AcSDKP excretion and plasma AcSDKP concentration after administration of perindopril, with significant between-period differences (estimate of the median difference in urinary excretion over 48h of AcSDKP, 49.1 [95% CI: 15.3–82.0] nmol for 14 versus 10mg, and 73.2 [95% CI: 44.9–106.3] nmol for 20 versus 14mg). Consequently, a dose-dependent increase in plasma active renin concentration was observed. Even though each dose of perindopril 10 to 20mg was associated with a significant 24-h ambulatory blood pressure reduction versus placebo, no dose-dependency was detected in these normotensive subjects. Administration of perindopril arginine 10, 14, or 20mg to mildly sodium-depleted healthy volunteers is associated with a dose-dependent inhibition of in vivo ACE activity with significant between-dose differences. This effect was associated with a dose-dependent increase in plasma active renin concentration, indicating a dose-dependent blockade of the renin angiotensin system.